2016
DOI: 10.4312/dp.43.13
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and homogeneity among the early farming communities of Western Anatolia

Abstract: Our knowledge of the Neolithisation of Western Anatolia has increased considerably in recent years. Being located beyond, but on the border of the formative zone of Neolithisation, the region has acted as a buffer in the dispersal of the Neolithic way of life farther to the west. Recent research in Western Anatolia has shown that Neolithic sites appeared in the second quarter of the 7th millennium BC and had become widespread by the second half of the same millennium. There is now adequate data available on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…present-day Greece. Based on material culture analyses, some scholars suggested that Greece was colonised by Levantine agriculturalists moving along the coast (Perlès, 2005), while others pointed to Anatolian origins (E. Özdoğan, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…present-day Greece. Based on material culture analyses, some scholars suggested that Greece was colonised by Levantine agriculturalists moving along the coast (Perlès, 2005), while others pointed to Anatolian origins (E. Özdoğan, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Only post-7000 BCE did fully sedentary villages start appearing in W Anatolia. By c.6500 BCE, these carried the full “Neolithic package” of permanently inhabited buildings, agriculture, domestic animals, pottery, and specific ritual elements that eventually dispersed into Europe [reviewed in (Brami, 2015; Düring, 2011; Karul, 2019; Özbal & Gerritsen, 2019b; E. Özdoğan, 2016; M.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses have been formulated about a merging of forager and farmer groups in Northwest Anatolia (M. Özdogan 2013; 2014), but the supporting evidence at hand is far from concrete. Differences in architectural styles and material culture have led to theories regarding the presence and continuity of local pre-Neolithic communities at some sites (Düring 2013;Özbal, Gerritsen 2019;E. Özdogan 2016).…”
Section: Introductionmentioning
confidence: 99%